Hubungan Dukungan Informatif, Emosional, dan Pengetahuan dengan Kepatuhan Minum Obat TB Paru di Puskesmas Kecamatan Duren Sawit - Emilia, Emilia; Anwar, Syamsul; Badriah, Siti (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT In 2023, according to the global TB Report, Indonesia will still be in second place after India and China in third place with 1,060,000 cases. Mostly found in West Java, Central Java, East Java and 4th place DKI Jakarta with 28,125 TB cases. This research is to determine the relationship between informative, emotional and knowledge support with medication compliance in adult clients with pulmonary TB at the Duren Sawit District Health Center, East Jakarta. The design used is cross-sectional (cross-sectional) with a quantitative approach. The population was all pulmonary TB clients of productive age (15 to 59 years) who had undergone treatment for ≥ 1 month, there were 74 respondents, at the Duren Sawit District Health Center, East Jakarta. The results of the Multivariate Test Modeling on the emotional support variable showed that the p value was > α (p value = 0.021), while the p value of income was ≤ α (p value = 0.036). There is a relationship between informative support, emotional support, knowledge, education, employment and income with medication compliance in adult clients with pulmonary TB at the Duren Sawit District Health Center, East Jakarta with a p-value of 0.001. Suggestion: Families should always increase emotional support for pulmonary TB clients regarding recovery. Keywords: Informative Support, Emotional, Knowledge, Compliance  ABSTRAK Pada tahun 2023 menurut global TB Report, indonesia masih menempati posisi kedua setelah india dan China posisi ketiga dengan kasus sebanyak 1.060.000. Banyak di temukan di Jawa Barat, Jawa Tengah, Jawa Timur dan urutan ke 4 DKI Jakarta sebanyak 28.125 kasus TB. Penelitian ini adalah untuk mengetahui hubungan dukungan informatif, emosional dan Pengetahuan dengan kepatuhan minum obat klien dewasa dengan TB Paru di Puskesmas Kecamatan Duren Sawit Jakarta Timur. Desain yang digunakan cross-sectional (potong lintang) dengan pendekatan kuantitatif. Populasinya seluruh klien TB paru usia produktif (15 s.d. 59 tahun) yang sudah menjalani pengobatan ≥ 1 bulan ada 74 responden, di Puskesmas Kecamatan Duren Sawit Jakarta Timur. Hasil Permodelan Uji Multivariat pada variabel dukungan emosional didapatkan nilai p value > α (p value = 0.021), sedangkan pendapatan nilai p value ≤ α (p value = 0.036). Ada hubungan dukungan informatif, dukungan emosional, pengetahuan, Pendidikan, pekerjaan dan pendapatan dengan kepatuhan minum obat klien dewasa dengan TB paru di Puskesmas Kecamatan Duren Sawit Jakarta Timur dengan p-value 0.001. Saran: Keluarga senantiasa meningkatkan dukungan emosional terhadap klien TB paru terkait kesembuhan. Kata Kunci: Dukungan Informatif, Emosional, Pengetahuan, Kepatuhan